Bibliometric Analysis of Cooperative Learning's Impact on Critical Thinking Skills in Computer Applications Courses in Vocational Education - Elsa Sabrina; Rosma Siregar; Saras Pratama (Jurnal Vokasi Teknik Informatika, 2025)
This study aims to map the trends and developments in the literature regarding the influence of Cooperative Learning on enhancing students’ Critical Thinking skills within the context of Vocational Education, using a bibliometric approach and a systematic literature review (SLR). The bibliometric analysis was conducted using R Studio, while keyword network visualization was performed using VOSviewer. The findings indicate that the peak of citations occurred in 2016, and the highest number of publications was recorded in 2022, with an average of 2.7 authors per article, reflecting significant multidisciplinary collaboration. The keyword visualization reveals a strong interrelation between cooperative learning, critical thinking, and vocational education, forming the core cluster of the research. These findings highlight the importance of cooperative learning as a strategic approach in developing vocational students' critical thinking skills and recommend the development of evidence-based implementation guidelines, contextual field research, and cross-sector collaboration to optimize its application in educational practice.